Implementation of Didactic Principles in Environmental Education - Sobczyk, Wiktoria (Theoretical and Methodical Problems of Children and Youth Education, 2025)
The article analyzes the current state of environmental education in the EU and, in particular, in Poland, as well as the main methods and principles for achieving the main goal of pro-environmental education. The purpose of the publication is to study the state of environmental education in Poland, which is an integral element of socio-economic programs aimed at implementing a new ecological era. Achieving the goal involves the implementation of the following tasks: studying the state of implementation of environmental disciplines in curricula and non-traditional educational activities, studying the process of pedagogical and educational influence on people to form their consciousness, personality and environmental attitudes, popularizing environmental problems among children and youth and forming environmental attitudes for the National Environmental Policy, improving environmental education as a component of the multifaceted development of the human personality, understanding threats, sensitivity to the destruction of the natural environment and reactions to its degradation. The theoretical basis comprises international and domestic materials on the impact of environmental education on the formation of quality and lifestyle in Poland and worldwide, as well as scientific works by scholars devoted to the study of the formation of environmental consciousness and culture. To achieve the set goal, the following research methods were used: monographic (analysis of scientific publications, in particular the author's publications); abstract-logical (theoretical generalizations and the formulation of conclusions); analogies and comparisons, etc. The importance of environmental knowledge in the formation of emotional-affective attitudes for the development of education seekers’ personalities, and the importance of the teacher’s role in achieving the depth of the listener’s spiritual sphere, are proven. It is found that the goals of education serve as a reference point for everything to be compared and evaluated. They have a regulatory meaning (guarantee against excessive expansion of resources) and an organizational meaning (educational structures and programs, methods, and means of teaching), give human meaning to the knowledge transmitted, and, at the same time, motivate those who strive to gain knowledge. They have a coordinating nature, strengthen and stimulate enthusiasm, inspire, and lead to the future. The article demonstrates the validity of the ecocentric idea and the importance of the modernized view that the highest good is the harmonious development of man and nature (people are part of nature). The author gives practical examples of the implementation of didactic principles of environmental education. The project for the development of environmental education aimed to build an educational system and identify the skills that should be developed, and it is already demonstrating the effective consequences of changing Europeans' consciousness.